Pain and Associated Substance Use among Opioid Dependent Individuals Seeking Office‐Based Treatment with Buprenorphine–Naloxone: A Needs Assessment Study. (25th April 2013) - Barry, Declan T.; Savant, Jonathan D.; Beitel, Mark; Cutter, Christopher J.; Moore, Brent A.; Schottenfeld, Richard S.; Fiellin, David A.
<x xml:space="preserve">Abstract</x> Background and Objectives A paucity of studies has examined the pain experiences of opioid dependent individuals seeking office‐based buprenorphine‐naloxone treatment (BNT). We set out to examine, among those seeking BNT: (a) the prevalence of pain types (i.e., recent pain, chronic pain), (b) the characteristics of pain (intensity, frequency, duration, interference, location, and genesis), and (c) substance use to alleviate pain. Method We surveyed 244 consecutive individuals seeking office‐based BNT for opioid dependence about physical pain and associated substance use. Results Thirty‐six percent of respondents reported chronic pain (CP) (i.e., pain lasting at least 3 months) and 36% reported "some pain" (SP) (i.e., past week pain not meeting the threshold for CP). In comparison to SP respondents, those with CP were, on average, older; reported greater current pain intensity, pain frequency, typical pain duration, typical pain intensity, and typical pain interference; were more likely to report shoulder or pelvis and less likely to report stomach or arms as their most bothersome pain location; and were more likely to report accident or nerve damage and less likely to report opioid withdrawal as the genesis of their pain. Both pain subgroups reported similarly high rates of past‐week substance use to alleviate pain. Conclusions and Scientific Significance The high rates of pain and self‐reported substance use to manage pain suggest the importance of assessing and addressing pain in BNT patients. (Am J Addict 2013; 22:212–217)